2013 IEEE International Conference on Sensing, Communications and Networking (SECON) 2013
DOI: 10.1109/sahcn.2013.6644968
|View full text |Cite
|
Sign up to set email alerts
|

Distributed MAC and rate adaptation for ultrasonically networked implantable sensors

Abstract: Abstract-The use of miniaturized biomedical devices implanted in the human body and wirelessly internetworked is promising a significant leap forward in medical treatment of many pervasive diseases. Recognizing the well-understood limitations of traditional radio-frequency wireless communications in interconnecting devices within the human body, in this paper we propose to develop network protocols for implantable devices based on ultrasonic transmissions. We start off by assessing the feasibility of using ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…Based on these observations, in [2] we proposed Ultrasonic WideBand (UsWB), a new impulse-radio inspired ultrasonic transmission and multiple access technique based on the idea of transmitting short information-bearing carrierless ultrasonic pulses, following a pseudo-random adaptive time-hopping pattern with a superimposed spreading code of adaptive length. Impulsive transmission and spread-spectrum encoding combat the effects of multipath and scattering and introduce waveform diversity among interfering transmissions.…”
Section: B Ultrasonic Widebandmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on these observations, in [2] we proposed Ultrasonic WideBand (UsWB), a new impulse-radio inspired ultrasonic transmission and multiple access technique based on the idea of transmitting short information-bearing carrierless ultrasonic pulses, following a pseudo-random adaptive time-hopping pattern with a superimposed spreading code of adaptive length. Impulsive transmission and spread-spectrum encoding combat the effects of multipath and scattering and introduce waveform diversity among interfering transmissions.…”
Section: B Ultrasonic Widebandmentioning
confidence: 99%
“…Given the limitations of RF propagation, in [1], [2] we proposed and investigated the use of ultrasonic waves as an alternative carrier of information in human tissues. Lowfrequency acoustic waves (up to 100 kHz) have found application in underwater communications [5], while ultrasounds at higher frequencies are extensively used in medical imaging applications [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8], [9], we showed that ultrasonic waves have a strong potential to enable internetworking among devices implanted in the human body at communication ranges spanning from few µm to several cm; while in [10] the authors, based on consideration on the physics of ultrasound propagation, investigate the power requirements for acoustic communications between nanorobots across various distances and tissues. However, as of today and to best of our knowledge, no existing studies have explored the feasibility of ultrasonic wave generation and detection at the nanoscale for communication purposes.…”
Section: Introductionmentioning
confidence: 99%